2019
DOI: 10.1002/hpm.2782
|View full text |Cite
|
Sign up to set email alerts
|

Health care expenditure for delivery care between maternity waiting home users and nonusers inEthiopia

Abstract: Summary Objective To compare the health care expenditures between maternity waiting home (MWH) users and nonusers in Ethiopia. Methods A cross‐sectional study was done in Ethiopia between December 2017 and June 2018. The study setting included eight health facilities in the Gurage zone of Ethiopia. Health expenditure for delivery care was the outcome variable that was then classified into out‐of‐pocket (OOP) payments, women's costs, total costs, and overall costs. Those health expenditures were then compared a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…Women in the age group of 19 to 40 years have higher incidence of hospitalization. This is consistent with other studies which show that women in the reproductive age group have higher rates of hospitalizations and incur higher health expenditures (49,50).…”
Section: Discussionsupporting
confidence: 93%
“…Women in the age group of 19 to 40 years have higher incidence of hospitalization. This is consistent with other studies which show that women in the reproductive age group have higher rates of hospitalizations and incur higher health expenditures (49,50).…”
Section: Discussionsupporting
confidence: 93%
“…Then, 27 articles with a sample size of 331,537 participants were included to assess determinants of the burden of household Out-Of-Pocket healthcare expenditures. Of these, six articles were conducted at the national level [ 13 , 33 – 37 ]. The remaining 21 articles were conducted in different parts of Ethiopia: i.e., six articles were conducted in the south regional state [ 14 , 33 – 37 ], five articles in Amhara regional state [ 38 42 ], five articles in Addis Ababa city [ 43 47 ], three articles in Oromiya regional state [ 48 – 50 ], one article in Bensangual-Gumuz regional state [ 51 ], and one article in a combination of Afar and Oromiya regional states [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the authors found major differences between MWH users and non-users, whereas our analysis showed very few. 24 They concluded that MWH users have significantly higher OOP costs than nonusers, but we believe this difference emerged from different sampling frames and methodology. 24 Overall, our findings suggest that, for women living most remotely who deliver at rural health facilities in Zambia, using a MWH does not cost significantly more than delivering at a rural health facility without using a MWH when considering key categories of common delivery-related expenses.…”
Section: Discussionmentioning
confidence: 93%
“…Yet, there is little empirical evidence on whether expenditure differences exist between those who use MWHs and those who do not (referred throughout the rest of this paper as 'users' and 'non-users' respectively). 24 Within a broader impact evaluation of the MHA, we analyzed self-reported OOP expenditure for women living remotely who recently delivered at a health facility. We compared OOP spending of women who stayed at MWHs and those who did not for their most recent delivery to better understand how MWH use factors into OOP expenditure for facility delivery among socioeconomically disadvantaged women in rural Zambia.…”
mentioning
confidence: 99%